Korupsi Di Peradilan: Kendala dan Tantangan dalam Pemberantasan Korupsi - Asrianto Zainal (Institut Agama Islam Negeri (IAIN) Kendari, 2009)
The result of this research finding indicates that in the effort executing eradication of corruption in Indonesia hence Eradication of corruption have to be executed with [is] same governmental and people because without the participation of public and of political will of government hence desire to make free and clean new Indonesia of KKN will not form. For the reason simultan with the effort of lis straightening of law hardly and coherent which accompanied by bureaucracy reform hence require to wake up by a collective awareness that corruption is enemy of big with which must be fought against.